2014
DOI: 10.15452/cejnm.2014.05.0011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of music listening on preoperative state anxiety and physiological parameters in patients undergoing general surgery: a randomized quasi-experimental trial

Abstract: Aim: The aim of the present study was to evaluate the effects of music on preoperative state anxiety and physiological parameters including heart rate, respiratory rate and mean systolic, and diastolic blood pressure in 60 patients undergoing general surgery. Methods: The study was designed as a randomized quasi-experimental trial. A total of 60 patients were allocated to two equal groups. Subjects in the trial group listened to non-vocal classical music through headphones for 20 minutes before entering the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
1
11
0
2
Order By: Relevance
“…These findings are positive, since they point to the possibility of having a low cost intervention that allows greater well-being and quality of life for these patients. These results also agree with other studies performed with patients during invasive procedures that demonstrate that listening to music significantly relieves the perceived levels of anxiety 12 , 22 . Review and meta-analysis studies also complement by pointing out the effectiveness of musical intervention to reduce physiological and psychological stressors experienced by patients submitted to procedures in outpatient clinics 16 , hemodialysis 19 , perioperative period 15 and burned patients 28 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These findings are positive, since they point to the possibility of having a low cost intervention that allows greater well-being and quality of life for these patients. These results also agree with other studies performed with patients during invasive procedures that demonstrate that listening to music significantly relieves the perceived levels of anxiety 12 , 22 . Review and meta-analysis studies also complement by pointing out the effectiveness of musical intervention to reduce physiological and psychological stressors experienced by patients submitted to procedures in outpatient clinics 16 , hemodialysis 19 , perioperative period 15 and burned patients 28 .…”
Section: Discussionsupporting
confidence: 92%
“…The music chosen for the study belongs to a musical genre that is not among the musical preferences of the majority of the Brazilian population, perhaps because of the difficult access to classical productions. This fact does not undermine the choice though, because the objective of this research was to prove the therapeutic effect of music in the reduction of anxiety as based on international studies 12 , 24 ) which have confirmed the effective results with this musical genre. Moreover, one study corroborates that the use of music of the patient’s preference did not present a statistically significant effect on anxiety when compared to classical music (p = 0.769) 29 .…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations